Financial Analysis under the Possibility of Uncertainty - Rutkauskas, Aleksandras Vytautas (Ekonomika, 2001)
The uncertainty and the risk related - are not only the attributes of the perspective, the empirical vision of the environment surrounding us - it is a random illustration. This is declared by one of the oldest spheres of the science and the practice - measurement theory and practice, which declare that any measurement as an act of the empirical cognition never is completely precise and can be interpreted as a random parameter. The scale of indetermination increases when the future possibilities are analyzed. Financial accounting, analysis and auditing as a knowledge system about the business state and development possibilities, arc based on measurement and forecasting. So the empirical recognition of the analyzed object as well as foreseeing of their possibilities in future - it is the structural description of their possible states totality, using the probability distribution of those possibilities. The conception of the financial analysis performance is presented in this work under possibilities of uncertainty also the system of the imitative models are suggested by the help of which the financial analysis can be performed under the uncertainty and the risk correspondingly.